Morphological and transcriptomic analyses reveal three discrete primary stages of postembryonic development in the common fire salamander, Salamandra salamandra. Issue 2 (5th March 2018) - Sanchez, Eugenia; Küpfer, Eliane; Goedbloed, Daniel J.; Nolte, Arne W.; Lüddecke, Tim; Schulz, Stefan; Vences, Miguel; Steinfartz, Sebastian
Abstract: The postembryonic development of amphibians has been characterized as divided into three predominant periods, hereafter named primary developmental stages: premetamorphosis (PreM), prometamorphosis (ProM), metamorphic climax (Meta), and completion of metamorphosis (PostM), largely based on examination of anuran development. Here, we categorized the postembryonic development of larvae of a poisonous fire salamander ( Salamandra salamandra ) by integrating morphology and gene expression (transcriptomic) data. Morphological analysis revealed three distinct clusters suggestive of PreM, ProM, and Meta, which were confirmed in parallel by microarray‐derived gene expression analysis. In total, 3, 510 probes targeted transcripts differentially expressed between the clusters we identified. Genes upregulated in PreM related to organogenesis, and those upregulated in Meta underlie structural proteins and related to development of anatomical structures and pigmentation. Biosynthesis pathways of pigments (pteridines and melanin) were upregulated during late ProM and Meta. Gas chromatographic analysis of alkaloids indicated the onset of steroidal alkaloid biosynthesis at ProM. When comparing gene expression in the fire salamander to that in other amphibians—three anurans, Xenopus laevis, X. tropicalis, and Michrohyla fissipes, and one caudate, Ambystoma mexicanum— we identified genes with conserved expression patterns involved in basic metamorphic processes such as skin restructuring and tail fin resorption. Our results support that primary stages of postembryonic development in caudates are homologous to those of anurans, and offer a baseline for the study of the evolution of developmental modes. GRAPHICAL ABSTRACT: Morphology and transcriptomics of salamander larval development correlated with pre‐, pro‐metamorphosis, and metamorphic climax. Comparative analysis supports this as conserved in amphibians. Alkaloid synthesis appears to start at prometamorphosis.